2017
DOI: 10.14445/23942568/ijaes-v4i4p109
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of the Mayurakshi River System Water Quality – the Agrarian Basin

Abstract: The Mayurakshi River system is an important interstate river system in India, and is widely exploited for various purposes. A preliminary assessment of the water quality of the Mayurakshi system, at eleven strategically selected locations in the West Bengal (India), was carried out. Most of the water quality parameters were found to be within the regulatory limits of the recommended standards and other indices, including water quality index (WQI). The WQI values varied from 70.45 to 84.09, and designated the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the present study, report of a few uncommon genera and species including discovery of new species from Mayurakshi River indicates healthy sustainable environment for survivability of fish species. This can be endorsed by the study of Ghosh et al [29] who showed that limited humaninfluenced disturbance of the water quality of the Mayurakshi riverine system. On the basis of utilization criteria of the river water viz.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the present study, report of a few uncommon genera and species including discovery of new species from Mayurakshi River indicates healthy sustainable environment for survivability of fish species. This can be endorsed by the study of Ghosh et al [29] who showed that limited humaninfluenced disturbance of the water quality of the Mayurakshi riverine system. On the basis of utilization criteria of the river water viz.…”
Section: Discussionmentioning
confidence: 85%
“…On the basis of utilization criteria of the river water viz. degree of domestic use, agricultural practices and fisheries, the water quality of this river was found ecologically sustainable with self-purification capacity [29] . Though in recent years, illegal sand mining in the river bed poses a great threat in the natural flow of the river and in some area, it changes the natural habitat and niche of the small fishes.…”
Section: Discussionmentioning
confidence: 95%